Association between adverse perinatal outcomes and sleep disturbances during pregnancy: a systematic review and meta-analysis. (2nd January 2022) - Yang, Ziyi; Zhu, Ziyu; Wang, Chunyi; Zhang, Fan; Zeng, Huan
Abstract: Background: Due to physiological and hormonal factors, sleep disturbances are prevalent in the obstetric population. Multiple studies have evaluated the relationship between sleep disturbances and perinatal outcomes, with inconsistent results. The purpose of this systematic review and meta-analysis was to further assess the overall relationship between four types of sleep disturbances (snoring, obstructive sleep apnea, extreme sleep duration, and poor sleep quality) and adverse perinatal outcomes. Methods: We performed electronic searches in PubMed, Embase, the Cochrane Library, CNKI, VIP, and Wanfang Data in February 2019 to identify studies that assessed adverse perinatal outcomes among expectant mothers with sleep disturbances. Results: In total, 5044 studies were identified in the initial search and 65 met the defined criteria. Pooled analysis showed that sleep disturbances were associated with an increased risk for preeclampsia (aOR: 2.77; 95% CI: 1.81–4.24), gestational diabetes mellitus (aOR: 1.96; 95% CI: 1.62–2.38), cesarean delivery (aOR: 1.99; 95% CI: 1.70–2.33), depression (aOR: 3.98; 95% CI: 2.74–5.77) and preterm birth (aOR: 1.95; 95% CI: 1.55–2.45). Conclusions: The four studied sleep disturbances (OSA, snoring, extreme sleep duration and poor sleep quality) during pregnancy were associated with adverse perinatal outcomes. Expectant mothers should be advised to practice healthy sleep hygiene measures.